1996
DOI: 10.1074/jbc.271.52.33335
|View full text |Cite
|
Sign up to set email alerts
|

24R,25-(OH)2 Vitamin D3 Inhibits 1α,25-(OH)2 Vitamin D3 and Testosterone Potentiation of Calcium Channels in Osteosarcoma Cells

Abstract: Calcium influx via L-type calcium channels in osteoblast cells causes a rapid (in seconds) elevation in intra-A newly described function of 1␣,25-D 3 1 and its analogues is the rapid (in seconds) regulation of intracellular calcium concentration, first reported in chicken duodenum (1) and later in bone osteoblast cells (2-12). It has been documented by patch clamp recordings of whole-cell barium currents (2, 3), by 45 Ca 2ϩ uptake (5, 7), and by fluorescence measurements of intracellular calcium, using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…L-type Ca 2+ channels as a target for 24R,25(OH) 2 D 3 action have previously been reported in ROS 17/2·8 cells (Caffrey & Farach-Carson 1989, Yukihiro et al 1994, Takeuchi & Guggino 1996 and UMR 106 cells (Li et al 1997). In ROS 17/2·8 cells, 24R,25(OH) 2 D 3 decreases the entry of calcium-45 and inhibits voltage-gated Ca 2+ channels at positive membrane potentials (Caffrey & Farach-Carson 1989, Yukihiro et al 1994.…”
Section: Effects Of 24r25(oh) 2 D 3 and 25(oh)d 3 On Enterocyte Ca 2mentioning
confidence: 99%
See 2 more Smart Citations
“…L-type Ca 2+ channels as a target for 24R,25(OH) 2 D 3 action have previously been reported in ROS 17/2·8 cells (Caffrey & Farach-Carson 1989, Yukihiro et al 1994, Takeuchi & Guggino 1996 and UMR 106 cells (Li et al 1997). In ROS 17/2·8 cells, 24R,25(OH) 2 D 3 decreases the entry of calcium-45 and inhibits voltage-gated Ca 2+ channels at positive membrane potentials (Caffrey & Farach-Carson 1989, Yukihiro et al 1994.…”
Section: Effects Of 24r25(oh) 2 D 3 and 25(oh)d 3 On Enterocyte Ca 2mentioning
confidence: 99%
“…This is in line with the findings of previous studies and seems to indicate a general phenomenon for cells in different Ca 2+ regulatory organs. In the chicken (deBoland & Norman 1990) and rat (Massheimer et al 1994) channels has also been demonstrated in osteoblasts (Caffrey & Farach-Carson 1989, Yukihiro et al 1994, Takeuchi & Guggino 1996, Li et al 1997 (Takeuchi & Guggino 1996). The physiological relevance of rapid, non-genomic effects on intestinal Ca 2+ transport and on mineralization processes in bone may be to enable a rapid regulation of free Ca 2+ concentrations in the blood and extracellular fluids.…”
Section: Effects Of 24r25(oh) 2 D 3 and 25(oh)d 3 On Enterocyte Camentioning
confidence: 99%
See 1 more Smart Citation
“…24,25(OH) 2 D 3 has not been as widely studied, perhaps because of the perception that it is an inactivation product. However, a growing body of literature has indicated that 24,25(OH) 2 D 3 has important effects in development (Henry & Norman 1978), bone (Sömjen et al 1983, Lidor et al 1987, Schwartz et al 1988, Swain et al 1993, Khoury et al 1995, Yukihiro et al 1994, Takeuchi & Guggino 1996, Ono et al 1996, Seo & Norman 1996, Kato et al 1998, and parathyroids (Carpenter et al 1996). More recently (Nemere 1996a(Nemere , 1999, it has been demonstrated that in chick intestine, 24R,25(OH) 2 D 3 inhibits the rapid stimulation of calcium transport mediated by 1,25(OH) 2 D 3 .…”
Section: Introductionmentioning
confidence: 99%
“…While 1,25-dihydroxyvitamin D 3 stimulates the rapid transport of calcium and phosphate in both perfused chick duodenal loops and isolated enterocytes, 24,25-dihydroxyvitamin D 3 inhibits such stimulation [3,4]. In osteoblasts and osteosarcoma cells, 1,25(OH) 2 D 3 has been found to have a rapid effect on calciumchannel-opening, while 24,25(OH) 2 D 3 was found to inhibit this nonnuclear effect [5][6][7]. In chick intestinal cells, 1,25(OH) 2 D 3 has been found to have an acute, non-nuclear effect on phosphate transport, and 24,25(OH) 2 D 3 has been found to inhibit the reaction [8], with no effect on parathyroid hormone (PTH) stimulated phosphate transport [9].…”
Section: Introductionmentioning
confidence: 99%